SHORT COMMUNICATION: PREVIOUSLY UNREPORTED HUMAN−PRIMATE CONFLICT IN KALISALAK FOREST, CENTRAL JAVA-INDONESIA - Nasution, Erie; Al Hakim, Rosyid; Aoliya, Nur (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
We found the phenomenon of human−primate conflict (HPC) in the Kalisalak Forest, Central Java, Indonesia. This location is also known locally as the research site of the Kalisalak Study Site or Kalisalak Grand Forest Park (KGFP) and is used for religious activities by local ethnicities. The research site is used for pilgrimages every Suro Month in the Islamic calendar. Based on the history adopted from the local people, the macaques already existed in the colonial period of the Dutch East Indies. We interviewed "caretakers", mentioning that there are about 75 to 100 long-tailed macaques, but an unusual phenomenon occurs in HPC. According to local people, this conflict is in the form of crop-raiding, expressing agonistic behaviour such as grimacing and chasing visitors. However, when we repeated observations for one month, there was no conflict between long-tailed macaques and humans. The recorded population is still one large group. Besides, to conserve long-tailed macaques and minimize the incidence of HPC, further research is needed to be related to the management of primates by considering the location of the grand forest park type as well as secondary forest types, with the main commodity of the community being forest products.